Achievement of forging without canning for β-solidifying γ-TiAl alloy containing high content of niobium. Issue 14 (26th October 2021) - Ge, Gengwu; Wang, Zeming; Liang, Siyuan; Zhang, Laiqi
ABSTRACT: The processes of forging without canning were optimized, such that forging could be successfully performed and forged pancakes without cracks could be obtained. The maximum height reduction could reach 80%. The as-forged microstructure consisted of γ and β/B2 phases. The volume fraction of the β/B2 phase rose slightly compared to the pre-forging state. Near the top or bottom of the pancake, residual lamellae were found, while full dynamic recrystallization was completed at the center and lateral parts. Equiaxed γ grains illustrated that dynamic recrystallization mainly occurred in the γ phase, while the softer β phase coordinated the deformation by adjusting morphology. Two types of Σ3 boundaries, [110] 70° and [111] 60°, were found in the γ phase. At room temperature, the fracture was brittle, and the elongation was 0.07%. With increasing temperature, the yield strength and ultimate strength decreased, while the elongation increased. The brittle–ductile transition temperature was between 800°C and 850°C.